Exosomal lncRNA ROR1-AS1 Derived from Tumor Cells Promotes Glioma Progression via Regulating miR-4686 - Chai Y; Wu HT; Liang CD; You CY; Xie MX; Xiao SW (International Journal of Nanomedicine, 2020)
Yang Chai, Hai-Tao Wu, Chuan-Dong Liang, Chun-Yue You, Ming-Xiang Xie, Shun-Wu Xiao Department of Neurosurgery, Affiliated Hospital of Zunyi Medical University, Zunyi, Guizhou 563000, People’s Republic of ChinaCorrespondence: Shun-Wu XiaoDepartment of Neurosurgery, Affiliated Hospital of Zunyi Medical University, Zunyi, Guizhou 563000, People’s Republic of ChinaEmail xiaoshunwu34576346@163.comObjective: Glioma is one of the most common central nervous system malignant tumors, accounting for 45%– 60% of adult intracranial tumors. However, the clinical treatment of glioma is limited. It is of great significance to seek new therapeutic methods for glioma via gene therapy.Materials and Methods: Microarray is used to identify the lncRNAs that are differentially expressed in glioma. The expression of long non-coding RNA (lncRNA) ROR1-AS1 and miR-4686 was detected by qRT-PCR. Exosomes were isolated from the supernatant of normal and cancerous cells, and TEM was used for exosomes identification. MTT assay, wound healing assay, transwell assay, and colony formation assay were used to detect the exo-ROR1-AS1 function on proliferation, migration, and invasion in glioma cells. Luciferase assay and RIP assay were used to identify the relationship between lncRNA ROR1-AS1 and miR-4686. The effect of exo-ROR1-AS1 on tumorigenesis of glioma was confirmed by the xenograft nude mice model.Results: ROR1-AS1 was up-regulated in glioma tissues, and the high expression of ROR1-AS1 indicated a poor prognosis in glioma patients. Interestingly, ROR1-AS1 was packaged into exosomes and derived from tumor cells. Functional analysis showed exo-ROR1-AS1 promoted the progression of glioma cell lines SHG44 and U251. Furthermore, ROR1-AS1 acted as a sponge of miR-4686 and inhibited its expression. Functionally, forced expression of miR-4686 removed the promoted effects of lncRNA ROR1-AS1 on glioma development. In vivo tumorigenesis experiments showed that exo-ROR1-AS1 promoted glioma development via miR-4686 axis.Conclusion: Our study suggested tumor cells derived exo-ROR1-AS1 promoted glioma progression by inhibiting miR-4686, which might be a potential therapeutic target for glioma clinical treatment.Keywords: glioma, lncRNA ROR1-AS1, exosome, miR-4686, tumorigenesis